Pengaruh Daun Sirsak dan Bawang Putih sebagai Pestisida Nabati terhadap Hama Bayam Belang BA 132 - Melo, Angelina Triandini Payung Datu; Lumowa, Sonja Verra Tinneke; Herliani, Herliani; Serena, Nelda Anasthasia (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Insect pest attacks are one of the main obstacles in cultivating striped spinach (Amaranthus tricolor L.), because they reduce the quality and quantity of the harvest. Long-term use of synthetic pesticides has a negative impact on the environment and health. This study aims to test the effectiveness of the combination of soursop leaf extract (Annona muricata L.) and garlic (Allium sativum) as a botanical pesticide on the intensity of pest attacks. The study was conducted using a Randomized Block Design (RBD) with five concentration treatments (0%, 25%, 45%, 65%, and 85%) and five replications. Data were analyzed using ANOVA and BNT test at the 1% level. The results showed that the botanical extract treatment had a significant effect on reducing the intensity of pest attacks, with a concentration of 85% giving the most effective results (Fcount 236.05 > Ftable 4.77). The treatment of plant leaves showed lower damage than the control. This effectiveness is thought to be due to the content of active compounds, such as flavonoids, saponins, tannins, acetogenins, and alkaloids which are toxic to pests. In conclusion, soursop leaf and garlic extracts have the potential to be environmentally friendly botanical pesticides and can be used as an alternative to control striped spinach plant pests.